A Review on Contact and Collision Methods for Multi-Body Hydrodynamic Problems in Complex Flows (Communications in Computational Physics, 2022)
Modeling and direct numerical simulation of particle-laden flows have atremendous variety of applications in science and engineering across a vast spectrumof scales from pollution dispersion in the atmosphere, to fluidization in the combustion process, to aerosol deposition in spray medication, along with many others. Dueto their strongly nonlinear and multiscale nature, the above complex phenomena stillraise a very steep challenge to the most computational methods. In this review, we provide comprehensive coverage of multibody hydrodynamic (MBH) problems focusingon particulate suspensions in complex fluidic systems that have been simulated usinghybrid Eulerian-Lagrangian particulate flow models. Among these hybrid models, theImmersed Boundary-Lattice Boltzmann Method (IB-LBM) provides mathematicallysimple and computationally-efficient algorithms for solid-fluid hydrodynamic interactions in MBH simulations. This paper elaborates on the mathematical framework, applicability, and limitations of various 'simple to complex' representations of close-contact interparticle interactions and collision methods, including short-range interparticle and particle-wall steric interactions, spring and lubrication forces, normal andoblique collisions, and mesoscale molecular models for deformable particle collisionsbased on hard-sphere and soft-sphere models in MBH models to simulate settling orflow of nonuniform particles of different geometric shapes and sizes in diverse fluidicsystems.